The EU-Emotion Stimulus Set: a validation study - O'Reilly, Helen; Bölte, Sven (Behavior research methods, 2016)
The EU-Emotion Stimulus Set is a newly developed collection of dynamic multimodal emotion and mental state representations. A total of 20 emotions and mental states are represented through facial expressions, vocal expressions, body gestures and contextual social scenes. This emotion set is portrayed by a multi-ethnic group of child and adult actors. Here we present the validation results, as well as participant ratings of the emotional valence, arousal and intensity of the visual stimuli from this emotion stimulus set. The EU-Emotion Stimulus Set is available for use by the scientific community and the validation data are provided as a supplement available for download.
Gesehen am 12.12.2019
Published online: 30 September 2015